Morphometric and molecular variation in concert: taxonomy and genetics of the reticulate Pyrenean and Iberian alpine spiny fescues (Festuca eskia complex, Poaceae). (13th November 2013) - Torrecilla, Pedro; Acedo, Carmen; Marques, Isabel; Díaz‐Pérez, Antonio José; López‐Rodríguez, José Ángel; Mirones, Victoria; Sus, Ana; Llamas, Félix; Alonso, Alicia; Pérez‐Collazos, Ernesto; Viruel, Juan; Sahuquillo, Elvira; et al.
<x xml:space="preserve">Abstract</x> The Iberian mountain spiny fescues are a reticulate group of five diploid grass taxa consisting of three parental species and two putative hybrids: F. × souliei (F. eskia × F. quadriflora) and F. × picoeuropeana (F. eskia × F. gautieri). Phenotypic and molecular studies were conducted with the aim of determining the taxonomic boundaries and genetic relationships of the five taxa and disentangling the origins of the two hybrids. Statistical analyses of 31 selected phenotypic traits were conducted on individuals from 159 populations and on nine type specimens. Molecular analyses of random amplified polymorphic DNA (RAPD) markers were performed on 29 populations. The phenotypic analyses detected significant differences between the five taxa and demonstrated the overall intermediacy of the F. × picoeuropeana and F. × souliei between their respective parents. The RAPD analysis corroborated the genetic differentiation of F. eskia, F. gautieri and F. quadriflora and the intermediate nature of the two hybrids; however, they also detected genetic variation within F. × picoeuropeana. These results suggest distinct origins for F. × picoeuropeana in the Cantabrian and Pyrenean mountains, with the sporadic Pyrenean populations having potentially resulted from recent hybridizations and the stabilized Cantabrian ones from older events followed by potential displacements of the parents. © 2013 The Linnean Society of London, Botanical Journal of the Linnean Society, 2013, 173, 676–706.